English Course Design for Students of Non-English Departments - Hompuraja Frans Susesco Saragih (Bandar Lampung University (UBL), 2013)
There have been increasing demands for English courses by non-English departments in Indonesia from year to year, either integrated in a curriculum as a compulsory subject, an optional course, or a special curriculum in a bilingual program. Whichever policy is taken, the objective is in order for the students to graduate with some English skills. One of the reasons for the demand is the increasing job vacancies that list a certain amount of English test score, mostly TOEFL, as a requirement. Both the reason and the objective, however, have so far been interpreted in curriculum as the need of English for English tests. In other words, an English course is needed in order to equip students should they are required to take an English test prior to job interview. This, I believe, is a case faced by most non-English departments in Indonesia.With such background, it is no wonder that English is considered as a mere subject which is apparent from the allocation of class hours. Students of non-English departments, which I assume to have weaker English competence and performance than those of English department, are given more or less 100 hours. Logically, if a student of English department is given more than 100 hours to sharpen his English skills, a student of non-English department should be given twice the hour, not less than that. It is not to mention when students are encouraged to take English courses outside university in which, in my opinion, it shows the lack of seriousness from the departments to provide intensive English courses. It seems that policy makers in non-English departments must be reminded of that English is a skill which, unlike knowledge, requires learning by doing and a long time process for fluency. Even a student of English department will experience degradation in competence and performance if he does not use his skill routinely. Therefore, English cannot, and should not, be learned just to pass an English test.Deriving from this point, policy makers and English teachers alike in non-English departments must design a curriculum and syllabus in which English should be studied for a longer and more frequent period of time (more than 3 semesters, 60-72 hours each semester) but with materials designed specifically for students of non-English departments and which is according to their field of study. The objective of this idea is for the students to achieve fluency in English naturally. With this much allocated time, students could begin studying basic skills of general English before they focus on English that is commonly used according to their field of study.This paper, then, offers a syllabus design for students of, specifically, Economics department. It is a design in which other non-English departments could modify according to their needs. With this intensive design, I believe, students can enhance their English skills that, even if they are not required to take an English test, they will not struggle in doing tasks that need English skills.